Crotalus morulus (Viperidae: Crotalinae) envenoming and treatment with F(ab')2 antivenom. (September 2022) - Grossart, EA; Walter, FG; Ashley, B.; Keyler, D.E.
Abstract: We present the first published case of Tamaulipan Rock Rattlesnake ( Crotalus morulus ) envenoming. A 54-year-old male professional herpetologist was bitten on the left thumb by a captive C. morulus . Pain, swelling, bruising, and pressure in the thumb were experienced within minutes. On presentation, he reported 7/10 pain and had firm edema in his thumb and thenar eminence. Initial laboratory studies showed normal platelet count, PT, PTT, and creatine kinase. He was treated with pain medication and 10 vials of crotalidae immune F(ab')2 (equine) antivenom approximately 3 h post envenoming. Lymphangitic streaking and axillary lymphadenopathy developed, followed by progression of edema, emergence of a hemorrhagic bulla, and declining platelets, prompting treatment with two additional 10-vial antivenom doses. His platelet count declined to 125 × 10 3 /μL 24 hours post envenoming and he developed numbness in his thumb. Following antivenom therapy completion no further decline in platelets occurred and thrombocytopenia improved to 131 × 10 3 /μL prior to discharge 46 hours post envenoming; fibrinogen, PT, PTT, and CK remained normal. He had no residual signs or symptoms 5 months later. C. morulus venom includes proteolytic venom enzymes that induce local soft tissue destruction, pain, and edema with ecchymosis and blister formation. Although C. morulus venom contains a unique disintegrin, morulustatin, no fibrinogenolytic activity was observed. Graphical abstract: Image 1 Highlights: Tamaulipan Rock Rattlesnake envenoming is previously unreported. Crotalus morulus is an uncommon Mexican species maintained in a few USA zoos and private collections. Rapid local tissue effects resulted after envenoming by a juvenile Crotalus morulus. F (ab')2 antivenom was effective in halting progression of local and systemic effects.